KASUS SUBDURAL HEMATOM DENGAN KERNOHAN NOTCH SYNDROME - Dherma Putra*, Syarif Indra**, Meiti Frida** (NEURONA, 2011)
CASE OF 53 YEARS OLD PATIENT WHO HAD A WEAKNESS OF RIGHT LIMBS AND FALLING OF RIGHT EYELID SINCE 3 DAYS PRIOR TO ADMISSION THERE WERE HEADACHE AND DOUBLE VISION BEFORE IT GENERAL EXAMINATION WAS NORMAL IN NEUROLOGIC EXAMINATION THERE WERE 3ND 7TH 12TH PALSIES HEMIPARESE DEXTRA KERNOHAN NOTCH SYNDROME INCREASED OF PHYSIOLOGIC REFLEXES POSITIVE PATHOLOGICAL REFLEXS IN THE RIGHT LIMBS AND BILATERAL PAPILEDEMA THE CT SCAN SHOWED HIPERDENSE LESION WITH CRESCENTSHAPED IN THE DEXTRA FRONTOTEMPOROPARIETAL REGION OBLITERATING RIGHT LATERAL VENTRICLE MIDLINE SHIFT TO THE LEFT NARROW GYRUS AND SULCUS NARROW VENTRICLES AND SISTERNA NORMAL SEREBELLUM PONS CPA WHICH CONCLUDED AS SUBDURAL HEMATOMA PATIENT WERE TREATED CONSERVATIVELY BY MANNITOL 20 AND BURR HOLE SURGERY